1995
DOI: 10.1006/aphy.1995.1055
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Groups, Coherent States, Squeezing and Lattice Quantum Mechanics

Abstract: By resorting to the Fock-Bargmann representation, we incorporate the quantum Weyl-Heisenberg algebra, q-WH, into the theory of entire analytic functions. The q-WH algebra operators are realized in terms of finite difference operators in the z plane. In order to exhibit the relevance of our study, several applications to different cases of physical interest are discussed: squeezed states and the relation between coherent states and theta functions on one side, lattice quantum mechanics and Bloch functions on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 23 publications
0
58
0
Order By: Relevance
“…We recall indeed that squeezed coherent states with different squeezing parameters (different slopes in Figs. 3 and 6) belong to different dynamical regimes (phases) [24]. It is interesting to observe that the linear behavior in log-log PDS/frequency plots in specific intervals of frequencies found in the present system, also appears in brain studies where assemblies (clusters) of large number of neurons with phase locked amplitude modulated oscillations and self-similarity properties are observed as well [25,26,27,28,29,30,21].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…We recall indeed that squeezed coherent states with different squeezing parameters (different slopes in Figs. 3 and 6) belong to different dynamical regimes (phases) [24]. It is interesting to observe that the linear behavior in log-log PDS/frequency plots in specific intervals of frequencies found in the present system, also appears in brain studies where assemblies (clusters) of large number of neurons with phase locked amplitude modulated oscillations and self-similarity properties are observed as well [25,26,27,28,29,30,21].…”
Section: Discussionmentioning
confidence: 69%
“…Note that |qα is actually a squeezed coherent state [24,16] with ζ = ln q the squeezing parameter. Thus, q N acts in F as the squeezing operator.…”
Section: Self-similarity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In fact it has been shown that it is possible to obtain a "coordinate" realization of the Fock space of the q-oscillators by using the deformed Jackson derivative (JD) or the so-called q-derivative operator [6,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…From the seminal work of Biedenharn [2] and Macfarlane [3], it was clear that the q-calculus, originally introduced in the study of the basic hypergeometric series [4,5,6], plays a central role in the representation of the quantum groups with a deep physical meaning and not merely a mathematical exercise. Many physical applications have been investigated on the basis of the q-deformation of the Heisenberg algebra [7,8,9,10,11]. In Ref.…”
Section: Introductionmentioning
confidence: 99%